Suppressing condensation frosting using micropatterned ice walls - Zuo, Zichao (2024)
Condensation frosting is encountered ubiquitously in our daily life and numerous industrial applications, rooting many detrimental consequences in heat transfer and mechanical stabilities. In latest decades, both active de-frosting and passive anti-frosting methods have been developed. In this work, we adopt the concept of three-dimensional overlapping dry zones by patterning microscopic ice walls on a smooth substrate, engendering a sustainable frost coverage of less than 13 %. Patterned ice walls prevent vapor deposition on the substrate base by absorbing all incoming moisture on upper sidewalls, leaving the substrate base free of contaminates from both frost and condensate. To ensure vapor preferentially depositing on upper sidewalls, a critical ice wall height exists, below which fine ice grains initiate in the adjacent of the substrate base and grow substantially faster, compromising the anti-frosting performance. The proposed surface shows reasonable durability when exposed to varying substrate supercooling, and frost coverage may increase due to covering and fracturing of the out-of-plane growth of feather-like ice clusters at large substrate supercooling. Our findings provide an effective anti-frosting surface design that doesn't require any chemical or mechanical modifications on the targeted surfaces, showing great advantages compared to conventional icephobic surface designs.